GSDMB/ORMDL3 variants contribute to asthma susceptibility and eosinophil-mediated bronchial hyperresponsiveness - Kang, Mi-Jin; Yu, Ho-Sung; Seo, Ju-Hee; Kim, Hyung-Young; Jung, Young-Ho; Kim, Young-Joon; Kim, Ha-Jung; Lee, So-Yeon; Hong, Soo-Jong (Human immunology, 2012)
In 2007, a genome-wide association study identified associations between variants involved in the regulation of ORMDL3 expression and asthma. These observations were subsequently replicated in case-control studies in several ethnic groups. We investigated the possible contribution of GSDMB/ORMDL3 variants to asthma susceptibility and intermediate asthma phenotypes in Korean children. The polymorphisms rs7216389, rs4794820, rs4065275, and rs11650680 were genotyped using the TaqMan assay in 931 asthmatics and 480 normal controls in a case-control study, and in 1907 elementary school children in a general population study. Each subject also underwent peripheral blood analysis of immunoglobulin E levels, eosinophil cationic protein (ECP) levels, and eosinophil percentage. Pulmonary function testing (FEV1 and MMEF) and a methacholine provocation test (PC20) were also performed. The case-control study revealed a significant association between a linkage disequilibrium block, including rs7216389, rs4794820, and rs4065275, and susceptibility to asthma and atopic asthma. The CT and TT genotypes of rs11650680 were associated with lower logECP levels than the CC genotype in asthmatics, while the GA and AA genotypes of rs4794820 were associated with higher logPC20 values than the GG genotype in atopic asthmatics. The haplotype (CAA) of rs7216389, rs4794820 and rs4065275 was associated with a lower risk of asthma susceptibility and a higher logPC20. In the general population study, rs11650680 was significantly associated with a diagnosis of asthma. Moreover, the GA and AA genotypes of rs4794820 were associated with higher logPC20 values and lower eosinophil percentages than the GG genotype in subjects who had been diagnosed with asthma, or showed bronchial hyperresponsiveness (PC20⩽16). The GSDMB/ORMDL3 gene block, which includes rs7216389, rs4065275, rs4794820, and rs11650680, may be associated with asthma susceptibility in Korean children because it promotes eosinophilic inflammation, which induces bronchial hyperresponsiveness.